AN ANALYSIS OF BALANCED SCORECARD AS TOOL OF MEASUREMENT PERFORMANCE AT THE BANK OF BENGKULU - Nadia Sigiro (Management Insight: Jurnal Ilmiah Manajemen, 2018)
The purpose in this research was one effort to help the perpetratorts business in asses the performance of the company (banking). Which is to know how the performance of PT.Bank of Bengkulu in the period 2013-2015 years, if viewd with the Balanced Scorecard approach. Based on the result measured performance used Balanced Scorecard method in Pt.Bank of Bengkulu viewed from the fourth perspective there were : 1. Perspective finance result of ratio ROA 2013 year amount 4,51%, 2014 year amount 3,69% and 2015 year amount 3,29% this can be said healthy. The result ratio BOPO 2013 year amount 526,35%, 2014 year amount 571,62% and 2015 year amount 593,99% this can be said unhealthy. The result ratio LDR 2013 year amount 104,05%, 2014 year amount 85,79% and 2015 year amount 91,05% this can be said healthy. 2. Customer perspective, the result from satisfaction of customer can be categorized satisfied at frequent 3,41-4,20 intervals. 3. Business perspective interval, the result from ratio AETR 2013 year amount 0,06% this can be said not good. 4. Perspective learning and growth, the result from productifitas employee 2013 year amount 19,81%, 2014 year amount 20,73% this can be said good. 2015 year amount 16,09% this can be said not good. Employee coaching 2013 year amount 0% this can be said not good, 2014 year amount 6,44% and 2015 year amount 16,09% this said good.Keyword: Performance, Balanced Scorecard, Bengkulu Banking